Bio-based foam material with super resilience as well as preparation and application of bio-based foam material
The bio-based foam material prepared by the wet foaming method uses natural wood fibers and bio-based synthetic fibers to solve the problem of cellulose-based foam material lacking resilience performance, and achieves a bio-based foam material with high resilience and stable performance, which is suitable for the dielectric layer of capacitive pressure sensors.
Patent Information
- Application Number
- CN202510127702.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-27
AI Technical Summary
Existing cellulose-based foam materials cannot return to their initial height after compression, and lack resilience, limiting their application range.
By adopting a wet foaming method, combining bioactive agents, biocrosslinkers and polyvalent metal salts, a biobased foam material consisting of natural wood fibers and biobased synthetic fibers is prepared. The material can be restored to its original shape after compression and has super rebound performance.
The bio-based foam material still maintains excellent strength and original shape after 10,000-40,000 compressions, significantly improving rebound performance, and maintaining stable performance in a wide temperature range and high humidity environment.
Smart Images

Figure CN119842197A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials and relates to a cellulose composite material, in particular to a bio-based foam material with super resilience and application of the bio-based foam material in a dielectric layer of a capacitor pressure sensor. Background Art
[0002] In the fields of wearable electronics, soft robots, human-machine interfaces, etc., there is an increasing demand for pressure sensors that respond to external mechanical stimuli and provide real-time information. Among them, the demand for capacitive pressure sensors has surged in recent years. This is because capacitive pressure sensors not only have a wide response range, but also have a simple structure. They are mainly composed of two conductive electrodes and a dielectric layer in the middle, similar to a sandwich structure. The change in capacitance (C) is achieved through the dielectric constant of the dielectric layer and the size of the capacitor; and the variability of the dielectric layer is the most critical influencing factor in capacitive sensing, which is usually achieved by adjusting the dielectric constant and compressibility of the dielectric layer. Therefore, the material used as the dielectric layer has a significant impact on the performance of the capacitive pressure sensor. At present, the dielectric layer of capacitive pressure sensors mostly uses low-density, high-surface-area polymer foams such as polyolefins, polyurethanes, polyamides, and polydimethylsiloxane. This is because the porous structure allows a lot of air to be contained inside, so the dielectric properties of the foam are close to those of air, so it is used as an air substitute in the dielectric layer of the sensor. However, these polymer foams are non-renewable and non-biodegradable. In order to achieve sustainable development, it is an inevitable trend to replace them with biodegradable materials.
[0003] Cellulose is the most abundant renewable biopolymer in nature and is considered an attractive candidate for the development of green and sustainable materials. Cellulose aerogel / foam has a lighter and more uniform porous structure and has been widely used in sensing research in recent years. Cellulose aerogels are mostly prepared from wet gels by freeze drying or supercritical drying, while cellulose-based foams are usually prepared by wet foaming with surfactants at room temperature and pressure, followed by molding and drying in air or an oven. Among them, cellulose aerogels mostly use nanoscale cellulose, such as cellulose nanocrystals, cellulose nanofibers, and bacterial cellulose. Pure nanocellulose aerogels exhibit 90% compressibility, and the application of freezing technology makes the aerogel have an anisotropic honeycomb structure, which gives the cellulose aerogel excellent mechanical strength and elasticity. Not only that, the aerogel can be given a directional structure by introducing strong covalent bonds, which is also an effective strategy to make the aerogel elastic. Due to its excellent elasticity and modifiable conductivity, aerogels have been successfully used in piezoresistive pressure sensors. However, the high price of nanofibers and the complicated subsequent processing technology (the use of toxic reagents, high-cost supercritical drying technology, etc.) have largely limited the application of pure nanocellulose aerogels.
[0004] In contrast to the excellent performance and high cost of cellulose aerogels, the cost of cellulose-based foams prepared by wet foaming with bioactive agents under normal pressure is significantly reduced. This is because: (1) the raw materials of cellulose-based foams are widely available, including waste paper fibers, pulp fibers, bamboo fibers, sugarcane bagasse, etc.; (2) the fiber sizes that can be used are larger, including nano-scale fibers, micro-scale fibers, and millimeter-scale fibers. However, it is well known that the preparation of cellulose-based foams has problems with wrinkles or deformation caused by water evaporation during the drying process, and the mechanical strength is poor and there is no resilience. Based on this, researchers have proposed solvent replacement (ethanol, acetone, etc.) or microwave-assisted drying methods to effectively solve the wrinkle or deformation problems caused by water evaporation. In addition, the improvement of the mechanical strength of cellulose-based foams is achieved through strategies such as constructing a cross-linked network, microfibrillating fibers, introducing functional coatings, and co-assembling at the gas-liquid interface; therefore, cellulose-based foams are also used in the fields of antibacterial, heat insulation, flame retardant, and sound insulation.
[0005] Currently, cellulose-based foam cannot recover to its original height after compression and lacks resilience. There is no report on any relevant solution, which limits its application to a certain extent. Summary of the invention
[0006] In view of the problem that cellulose-based foam in the prior art does not have resilience, the present invention provides a bio-based foam with super resilience and a preparation method thereof. The preparation method adopts a wet foaming method with a simple process, easy to scale up and low cost, which is not only low-cost, but also significantly improves the resilience of the cellulose-based foam, overcomes technical prejudice, and achieves unexpected technical effects. On this basis, the present application also provides the application of the bio-based foam as a dielectric layer of a capacitive pressure sensor, which can realize contact and non-contact sensing of pressure, has broad application prospects and huge economic value.
[0007] The technical solution of the present invention:
[0008] A bio-based foam material with super strong resilience, the foam material is composed of fiber raw material, bioactive agent, biocrosslinking agent and multivalent metal salt, and the fiber raw material is composed of natural wood fiber and bio-based synthetic fiber. Wherein, the length of the natural wood fiber is 1-3mm, the length of the bio-based synthetic fiber is 3-6mm, and the content of the bio-based synthetic fiber in the fiber raw material is not less than 50wt%. The natural wood fiber is one or more of coniferous wood pulp, broadleaf wood pulp, hemp pulp, cotton fiber, pineapple leaf fiber, banana stem fiber, bamboo pulp and bagasse pulp. The bio-based synthetic fiber is one or more of polylactic acid (PLA) fiber, polytrimethylene terephthalate (PTT) fiber, polyhydroxy fatty acid (PHA) fiber. The applicant unexpectedly found that by adding an appropriate amount of bio-based synthetic fiber with a length of 3-6mm, the resilience of the bio-based foam material finally prepared was significantly improved, and the excellent strength and original shape were still maintained after 10000-40000 compressions, achieving unexpected technical effects. The inventors have analyzed and speculated that this is because: compared with natural wood fibers, bio-based synthetic fibers have outstanding rigidity and toughness; under the aforementioned fiber length conditions, an intertwined structure is formed between the bio-based synthetic fibers and the natural wood fibers, so they will not be damaged during the compression process and have excellent rebound performance.
[0009] The hydrophile-lipophile balance (HLB) of the bioactive agent is 10-40, and the amount of the bioactive agent is 0.1-2.0wt% of the fiber raw material. Preferably, the bioactive agent is one or more of saponin, sulfonated lignin, amino lignin, carboxylated lignin, platycodon saponin, and liquiritin, and the amount of the bioactive agent is 0.3-1.5wt% of the fiber raw material.
[0010] The viscosity of the bio-crosslinking agent is 200±20mpa.s (1%, 2°C); the amount of the bio-crosslinking agent is 2-20wt% of the fiber raw material. Preferably, the bio-crosslinking agent is one or more of sodium alginate, carboxylated nanocellulose, and carboxymethyl cellulose; the amount of the bio-crosslinking agent is 2-10wt% of the fiber raw material.
[0011] The polyvalent metal salt is Ca 2+ Mg 2+ , Mn 2+ 、Al 3+ 、Zn 2+ , Fe 3+ and Cu 2+ One or more inorganic salts; the amount of the multivalent metal salt is 1-10wt% of the fiber raw material. Preferably, the amount of the multivalent metal salt is 3-10wt% of the fiber raw material.
[0012] As mentioned above, the bio-based foam material has a directional layered structure and interconnected macropores, its dielectric properties are similar to those of air, and it can recover its original shape after compression deformation, and has excellent resilience. Compared with the cellulose-based foam in the prior art, the technical effect is significantly improved. In addition, the bio-based foam material can maintain stable performance in a wide temperature range of -20°C to 150°C and in a high humidity environment, and has broad application prospects and considerable potential economic benefits.
[0013] As described above, the method for preparing the bio-based foam material adopts the strategy of wet foaming and ionic cross-linking to prepare the bio-based foam material with high resilience. Specifically, it includes the following steps:
[0014] (1) Dispersing fiber raw materials: Take appropriate amounts of natural wood fibers and bio-based synthetic fibers, disperse them in water, and obtain a fiber water dispersion, wherein the concentration of the fiber raw materials in the dispersion is 0.3-0.6 wt %. The stirring speed during the fiber dispersion is 100-1000 rpm, and the stirring time is 10-30 min.
[0015] (2) Foaming: Add bioactive agent and biocrosslinking agent to the fiber aqueous dispersion obtained in step (1), stir at room temperature to make the mixture uniform and fully foamed, and obtain a foam mixture, i.e., slurry. The stirring speed is 500-2000rpm, and the stirring time is 1-5min. In this step, by adding the biocrosslinking agent in advance, not only the crosslinking agent is evenly dispersed in the slurry, but also it helps foaming to a certain extent. In addition, the foaming process is carried out at room temperature and pressure, the amount of additives used is small and the cost is low, which has good economy.
[0016] (3) Cross-linking: Add a polyvalent metal salt solution to the foam mixture obtained in step (2), stir and mix at room temperature for cross-linking, then pour into a mold, filter to obtain wet foam, dry and shape to obtain the bio-based foam material. In this step, the cross-linking reaction mainly occurs between the polyvalent metal ions and the previously added bio-cross-linking agent.
[0017] Wherein, the stirring speed during the mixing and cross-linking is 100-500rpm, and the stirring time is 1-5min. The filtration is normal pressure filtration for 5-10min or vacuum filtration for 1-3h. The drying and molding is hot air drying or vacuum drying; the temperature of the hot air drying is 25-100℃, and the time of the hot air drying is 5-24h; the temperature of the vacuum drying is 30-60℃, and the drying time is 1-8h. In the preparation of cellulose-based foam in the prior art, if normal pressure drying is used, the foam will shrink and the structure will be destroyed, so freeze drying must be used. In contrast, in the preparation of the bio-based foam material described in the present application, even if conventional drying methods are used, the resilience of the foam material is not affected at all, which also verifies the significant improvement of its performance from another aspect.
[0018] As mentioned above, the bio-based foam material is used as the dielectric layer of the capacitive pressure sensor. Since the bio-based foam material has excellent resilience and porous structure, it fully meets the requirements of the dielectric layer of the capacitive pressure sensor. Moreover, compared with the pure nanocellulose aerogel in the prior art, it has the advantages of simple preparation method and significantly reduced cost, while having almost the same performance, and obviously has more competitive advantages.
[0019] A green and environmentally friendly capacitive pressure sensor, the sensor is assembled by an upper conductive layer, a lower conductive layer and an intermediate dielectric layer sandwiched between the upper conductive layer and the lower conductive layer according to a sandwich structure. The intermediate dielectric layer is the bio-based foam material as described above; the upper conductive layer and / or the lower conductive layer is a conductive copper tape with adhesiveness. The bio-based foam material is cut into rectangles of different sizes and laid flat on copper tapes of the same size to form a capacitive pressure sensor for contact and non-contact detection.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention first provides a bio-based foam material with super strong resilience. Compared with the cellulose-based foam in the prior art, the bio-based foam material has excellent resilience and can still maintain excellent strength and original shape after being compressed 10,000-40,000 times, achieving unexpected technical effects.
[0022] (2) The present invention also provides a method for preparing the bio-based foam material. The method uses natural wood fiber and bio-based synthetic fiber as main materials, which is not only simple in preparation and low in cost, but also green and environmentally friendly, and has good industrial application prospects.
[0023] (3) In view of the excellent resilience of the aforementioned bio-based foam material, it can be used as the dielectric layer of a capacitive pressure sensor to make a capacitive pressure sensor for contact and non-contact detection, thereby solving the technical problem of the raw materials used as the dielectric layer in the prior art being environmentally unfriendly / high in cost, and achieving huge economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Attached Figure 1 This is a physical picture of the bio-based foam material prepared in Example 1 of the present invention on a plant leaf.
[0025] Attached Figure 2 The radial and axial computer tomography images of the bio-based foam material prepared in Example 1 of the present invention.
[0026] Attached Figure 3 This is a stress-strain curve diagram of the bio-based foam material prepared in Example 1 of the present invention after being compressed by different deformations.
[0027] Attached Figure 4 This is a stress-strain curve of the bio-based foam material prepared in Example 1 of the present invention after 30,000 compressions at 50% compression deformation.
[0028] Attached Figure 5 This is the stress-strain curve of the bio-based foam material prepared in Example 1 of the present invention at different temperatures and humidities.
[0029] Attached Figure 6 This is a graph showing the mass change of the bio-based foam material prepared in Example 1 of the present invention before and after biodegradation.
[0030] Attached Figure 7 The actual picture and structural schematic diagram of the capacitive pressure sensor assembled with the bio-based foam material prepared in Example 1 of the present invention.
[0031] Attached Figure 8 This is a graph showing the relationship between the relative change in capacitance and strain of the capacitive pressure sensor described in Example 7 of the present invention.
[0032] Attached Fig. 9 This is a graph showing the relationship between the relative change in capacitance and time of the capacitive pressure sensor under contact detection according to Example 7 of the present invention.
[0033] Attached Fig.10 This is a graph showing the relationship between the relative change in capacitance and time of the capacitive pressure sensor under non-contact detection according to Example 7 of the present invention. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with the embodiments.
[0035] The following examples are only examples of embodiments of the present invention and do not constitute any limitation to the present invention. Those skilled in the art will appreciate that modifications or expansions within the scope of the spirit and concept of the present invention fall within the protection scope of the present invention.
[0036] Example 1: Preparation of bio-based foam material
[0037] Take 2.4g of polylactic acid (PLA) fiber and 0.6g of bleached conifer pulp to a 1000ml measuring cup, add 597ml of water and stir at room temperature for 30min, adjust the stirring speed to 500rpm, and obtain a fiber water dispersion; the concentration of the fiber raw material in the dispersion is 0.5wt%. Then add 24ml of 2wt% sodium alginate solution (accounting for 8wt% of the bio-based fiber) and bioactive agent saponin (0.01g, accounting for 0.3wt% of the bio-based fiber), continue stirring for 2min, and the stirring speed is 2000rpm to obtain a foam mixture, i.e., slurry. Finally, add 24ml of 2wt% calcium chloride solution (accounting for 8wt% of the bio-based fiber), continue stirring for 5min, and adjust the stirring speed to 100rpm. Pour the above mixture into a mold, filter at normal pressure for 1h to remove excess liquid and foam, and the obtained bio-based foam is placed at ambient temperature for 4h, and then hot-air dried in a 60℃ oven for 12h to obtain a dry superelastic green elastomer material bio-based foam material. The bio-based foam material is compressed under 50% deformation, and the shape recovery rate after 10,000 consecutive compressions is as high as 98%, and the shape recovery rate after 30,000 consecutive compressions is as high as 91%.
[0038] Example 2: Preparation of bio-based foam material
[0039] Take 2.1g of polytrimethylene terephthalate (PTT) fiber and 0.9g of bleached hardwood pulp into a 1000ml measuring cup, add 497ml of water and stir at room temperature for 10min, adjust the stirring speed to 1000rpm, and obtain a fiber water dispersion; the concentration of fiber raw materials in the dispersion is 0.6wt%. Then add 10ml of 3wt% carboxymethyl cellulose solution (accounting for 10wt% of bio-based fiber) and bioactive agent sulfonated lignin (0.012g, accounting for 0.4wt% of bio-based fiber), continue stirring for 3min, and the stirring speed is 1500rpm to obtain a foam mixture, i.e., slurry. Finally, add 10ml of 3wt% aluminum sulfate solution (accounting for 10wt% of bio-based fiber), continue stirring for 1min, and adjust the stirring speed to 500rpm. The above-mentioned mixed material was poured into a mold, and the excess liquid and foam were removed by vacuum filtration for 5 minutes. The obtained bio-based foam was placed at ambient temperature for 4 hours, and then vacuum dried in an oven at 60°C for 12 hours to obtain a dry bio-based foam material. The bio-based foam material was compressed under 50% deformation, and the shape recovery rate after 10,000 continuous compressions was as high as 96%. The shape recovery rate after 30,000 continuous compressions was as high as 91%.
[0040] Example 3: Preparation of bio-based foam material
[0041] Take 2.1g polyhydroxy fatty acid (PHA) fiber and 0.9g bleached bamboo pulp to a 1000ml measuring cup, add 747ml water and stir at room temperature for 20min, adjust the stirring speed to 800rpm, and obtain a fiber water dispersion; the concentration of fiber raw materials in the dispersion is 0.4wt%. Then add 10ml of 3wt% carboxylated nanocellulose dispersion (accounting for 10wt% of bio-based fiber) and bioactive agent platycodon saponin (0.012g, accounting for 0.4wt% of bio-based fiber), continue stirring for 5min, and the stirring speed is 500rpm to obtain a foam mixture, i.e., slurry. Finally, add 10ml of 3wt% zinc chloride solution (accounting for 10wt% of bio-based fiber), continue stirring for 2min, and adjust the stirring speed to 400rpm. Pour the above mixture into a mold, filter the liquid and foam removed by atmospheric pressure for 2h, and place the obtained bio-based foam at ambient temperature for 4h, and then dry it in a 50℃ oven for 14h to obtain a dry bio-based foam material. The bio-based foam material is compressed under 50% deformation, and the shape recovery rate after 30,000 consecutive compressions is as high as 91%, and the shape recovery rate after 40,000 consecutive compressions is as high as 90%.
[0042] Example 4: Preparation of bio-based foam material
[0043] Take 2g of polylactic acid (PLA) fiber and 1g of bleached coniferous wood pulp into a 1000ml measuring cup, add 797ml of water and stir at room temperature for 20min, adjust the stirring speed to 400rpm, and obtain a fiber water dispersion; the concentration of the fiber raw material in the dispersion is 0.38wt%. Then add 24ml of 2wt% sodium alginate solution (accounting for 8wt% of the bio-based fiber) and foaming agent sodium dodecyl sulfate (0.01g, accounting for 0.3wt% of the bio-based fiber), continue stirring for 3min, and the stirring speed is 1500rpm to obtain a foam mixture, that is, a slurry. Finally, add 24ml of 2wt% ferric chloride solution (accounting for 8wt% of the bio-based fiber), continue stirring for 3min, and adjust the stirring speed to 300rpm. Pour the above mixture into a mold, vacuum filter for 10min to remove excess liquid and foam, and the obtained bio-based foam is placed at ambient temperature for 4h, and then dried in a 60℃ oven for 12h to obtain a dry bio-based foam material. The bio-based foam material is compressed under 50% deformation, and the shape recovery rate after 15,000 consecutive compressions is as high as 93%, and the shape recovery rate after 30,000 consecutive compressions is as high as 92%.
[0044] Example 5: Preparation of bio-based foam material
[0045] Take 1.5g of polyhydroxy fatty acid (PHA) fiber and 1.5g of bleached hardwood pulp into a 1000ml measuring cup, add 663ml of water and stir at room temperature for 30min, adjust the stirring speed to 100rpm, and obtain a fiber water dispersion; the concentration of the fiber raw material in the dispersion is 0.45wt%. Then add 10ml of 3wt% carboxymethyl cellulose solution (accounting for 10wt% of the bio-based fiber) and bioactive agent amino lignin (0.012g, accounting for 0.4wt% of the bio-based fiber), continue stirring for 4min, and the stirring speed is 1000rpm to obtain a foam mixture, that is, a slurry. Finally, add 10ml of 3wt% copper chloride solution (accounting for 10wt% of the bio-based fiber), continue stirring for 5min, and adjust the stirring speed to 100rpm. Pour the above mixture into a mold, filter at normal pressure for 3h to remove excess liquid and foam, and the obtained bio-based foam is placed at ambient temperature for 4h, and then vacuum dried in a 60℃ oven for 12h to obtain a dry bio-based foam material. The bio-based foam material is compressed under 50% deformation, and the shape recovery rate after 30,000 consecutive compressions is as high as 93%, and the shape recovery rate after 40,000 consecutive compressions is as high as 90%.
[0046] Example 6: Characterization of the bio-based foam materials prepared in Examples 1-5
[0047] The bio-based foam materials prepared in Examples 1-5 were characterized, and the results were basically consistent; the bio-based foam material prepared in Example 1 is taken as an example for detailed description.
[0048] Attached Figure 1 This is a real picture of the bio-based foam material prepared in Example 1 of the present invention on a plant leaf. This can intuitively illustrate that it has the characteristics of low density and ultra-lightness.
[0049] Attached Figure 2 The radial and axial computed tomography images of the bio-based foam material prepared in Example 1 of the present invention are shown in FIG. Figure 2 It can be seen that the bio-based foam material exhibits different structures in the radial and axial directions, indicating that it has an anisotropic structure.
[0050] Attached Figure 3 The stress-strain curves of the bio-based foam material prepared in Example 1 after different deformation compressions. Figure 3 It can be seen that the foam can be compressed to a deformation of 90%, indicating its excellent compressibility.
[0051] Attached Figure 4 The stress-strain curve of the bio-based foam material prepared in Example 1 of the present invention after 30,000 compressions at 50% compression deformation. Figure 4 It can be seen that the bio-based foam material has a compression strength of 13 kPa. It can recover to its original shape after one compression and can still maintain 91% of its initial height after 30,000 compressions, which shows that the bio-based foam material has excellent resilience.
[0052] Attached Figure 5 The stress-strain curves of the bio-based foam material prepared in Example 1 of the present invention at different temperatures and humidities are shown in FIG. Figure 5 It can be seen that the bio-based foam material still has excellent resilience in an environment with a temperature of up to 150°C or a humidity of up to 95%, which indicates that it has excellent temperature and humidity stability.
[0053] Attached Figure 6 The mass of the bio-based foam material prepared in Example 1 of the present invention before and after biodegradation. Figure 6 It can be seen that the weight of the bio-based foam material is reduced by 85% of the initial weight after 50 days of composting degradation. It has excellent biodegradability and is an environmentally friendly bio-based material.
[0054] In summary, the bio-based foam materials prepared in Examples 1-5 can not only be compressed with a deformation of 90%, but also can maintain 91% of the initial height after 30,000 compressions at a compression deformation of 50%, and have excellent compressibility and resilience, which produces unexpected technical effects compared with the prior art. In addition, the aforementioned properties of the bio-based foam materials have excellent temperature stability and humidity stability, and also have excellent biodegradability, with broad industrial application prospects and huge economic value.
[0055] Example 7: Application of bio-based foam material as dielectric layer
[0056] The capacitive pressure sensor is prepared by using the bio-based foam material prepared in Examples 1-5. The structural design diagram and physical diagram of the capacitive pressure sensor are shown in Figure 7 .like Figure 7 As shown, the capacitive pressure sensor has a sandwich structure, including an upper conductive layer, a lower conductive layer, and an intermediate dielectric layer sandwiched between the upper and lower conductive layers; the intermediate dielectric layer uses the bio-based foam material prepared in Examples 1-5, and the upper conductive layer and the lower conductive layer are self-adhesive conductive copper tapes. The sensing performance of the above-mentioned capacitive pressure sensor was tested, and the test results were consistent. The following is an example of a capacitive pressure sensor using a bio-based foam material prepared in Example 1.
[0057] The real-time change of capacitance of capacitive pressure sensor was tested by Tonghui LCR impedance meter (TH2830). The results are shown in Figure 8 , Fig. 9 and Fig.10 Attached Figure 8 FIG. 1 is a graph showing the relationship between the relative change in capacitance and strain of the capacitive pressure sensor of the present invention. Figure 8 It can be seen that the prepared capacitive sensor has a stable signal output during the cyclic detection process. Fig. 9 This is a graph showing the relationship between the relative change in capacitance and time of the capacitive pressure sensor of the present invention under contact detection. Fig. 9 It can be seen that the prepared capacitive sensor has excellent stability during contact pressing, can detect a wide range of pressures from 0 to 80 kPa, and has different sensitivities in the pressure ranges of 0 to 21.7 kPa, 21.7 to 51.5 kPa, and 51.5 to 80 kPa. Fig.10 FIG. 1 is a graph showing the relationship between the relative change in capacitance and time of the capacitive pressure sensor of the present invention under non-contact detection. Fig.10 It can be seen that the prepared capacitive sensor also has a sensing signal when the tweezers are suspended in the air, and can be used for non-contact detection.
[0058] In summary, the capacitive sensor using the bio-based foam material prepared in Examples 1-5 as the dielectric layer is not only stable and reusable, with an adjustable thickness of the dielectric layer, but can also be used for contact and non-contact detection, and has good application prospects.
[0059] Comparative Example 1:
[0060] Unlike Example 1, no bio-based cross-linking agent and multivalent metal salt were added. The prepared bio-based foam had no compressive strength and collapsed instantly when subjected to 50% strain compression, which indicated that the ionic cross-linking effect of the bio-cross-linking agent helped the foam to have mechanical strength.
[0061] Comparative Example 2:
[0062] Unlike Example 1, no natural wood fiber is added. The prepared bio-based foam has a compression strength of 8.7 kPa. Although it is significantly improved compared with the bio-based foam prepared in Comparative Example 1, it will still collapse when subjected to 50% strain compression. The shape recovery rate of the foam after 10,000 continuous compressions is 87%. The shape recovery rate after 30,000 continuous compressions is 82%. The compression strength of the bio-based foam prepared in Example 1 is 13 kPa. It can not only be compressed with 90% deformation, but also can maintain 91% of the initial height after 30,000 compressions under 50% compression deformation. This shows that the use of only bio-based synthetic fibers not only reduces the resilience, but also the compression strength is not enough to meet the application requirements. It also shows that in the bio-based foams prepared in Examples 1-5 of the present application, natural wood fibers play a reinforcing role in the internal network of the foam, and their synergistic effect with the bio-based synthetic fibers enables the foam to have higher mechanical properties. There is no relevant report in the prior art, which produces unexpected technical effects.
[0063] Comparative Example 3:
[0064] Different from Example 1, no bio-based synthetic fiber is added, and the prepared bio-based foam is the cellulose-based foam in the prior art. This cellulose-based foam not only shrinks greatly in appearance after drying and cannot maintain its shape in the wet state, but also cannot recover to its original height after compression and has no resilience.
[0065] In summary, Examples 1-5 of the present application provide a method for preparing a bio-based foam material, which has low energy consumption, simple operation, and is green and environmentally friendly. In addition, the bio-based foam material prepared by the aforementioned method not only has a directional layered structure and interconnected macropores, but also has dielectric properties similar to those of air; it also has excellent resilience, with a rebound height retention rate of >90% after compression 10,000-40,000 times, and stable performance in a wide temperature range of -20°C to 150°C and a relative humidity of 0-100%, and has broad application prospects. Based on the aforementioned excellent performance, the capacitive pressure sensor prepared by the bio-based foam material has the advantages of high stability, wide detection range, and the ability to realize contact detection and non-contact detection.
Claims
1. A bio-based foam material with super strong resilience, characterized in that: The foam material is composed of fiber raw materials, bioactive agents, biocrosslinking agents and multivalent metal salts, wherein the fiber raw materials are composed of natural wood fibers and bio-based synthetic fibers; wherein the length of the natural wood fibers is 1-3 mm, the length of the bio-based synthetic fibers is 3-6 mm, and the content of the bio-based synthetic fibers in the fiber raw materials is not less than 50 wt %; the amount of the bioactive agent is 0.1-2.0 wt % of the fiber raw materials, the amount of the biocrosslinking agent is 2-20 wt % of the fiber raw materials, and the amount of the multivalent metal salt is 1-10 wt % of the fiber raw materials.
2. The bio-based foam material according to claim 1, characterized in that: The bio-based synthetic fiber is one or more of polylactic acid (PLA) fiber, polytrimethylene terephthalate (PTT) fiber, and polyhydroxyalkanoic acid (PHA) fiber.
3. The bio-based foam material according to claim 2, characterized in that: The hydrophile-lipophile balance (HLB) of the bioactive agent is 10-40; the viscosity of the biocrosslinking agent is 200±20mpa.s (1%, 2°C); the amount of the bioactive agent is 0.3-1.5wt% of the fiber raw material, the amount of the biocrosslinking agent is 2-10wt% of the fiber raw material, and the amount of the multivalent metal salt is 3-10wt% of the fiber raw material.
4. The bio-based foam material according to claim 3, characterized in that: The bioactive agent is one or more of saponin, sulfonated lignin, amino lignin, carboxylated lignin, platycodon saponin, and liquiritin; the biocrosslinking agent is one or more of sodium alginate, carboxylated nanocellulose, and carboxymethyl cellulose; the polyvalent metal salt is Ca 2+ Mg 2+ , Mn 2+ 、Al 3+ 、Zn 2+ , Fe 3+ and Cu 2+ One or more inorganic salts.
5. The bio-based foam material according to any one of claims 1 to 4, characterized in that: The natural wood fiber is one or more of softwood pulp, hardwood pulp, hemp pulp, cotton fiber, pineapple leaf fiber, banana stem fiber, bamboo pulp and bagasse pulp.
6. The method for preparing a bio-based foam material according to any one of claims 1 to 5, characterized in that: The steps include: (1) Dispersing the fiber raw materials: taking an appropriate amount of natural wood fiber and bio-based synthetic fiber, dispersing them in water to obtain a fiber water dispersion, wherein the concentration of the fiber raw materials in the dispersion is 0.3-0.6 wt %; (2) Foaming: adding a bioactive agent and a biocrosslinking agent to the fiber aqueous dispersion obtained in step (1), stirring at room temperature to mix uniformly and fully foam, to obtain a foam mixture; (3) Cross-linking: adding a polyvalent metal salt solution to the foam mixture obtained in step (2), stirring at room temperature for mixing and cross-linking, then pouring into a mold, filtering to obtain wet foam, and drying and molding to obtain the bio-based foam material.
7. The preparation method according to claim 6, characterized in that: The stirring speed during fiber decomposition and dispersion in step (1) is 100-1000 rpm, and the stirring time is 10-30 min; the stirring speed during foaming in step (2) is 500-2000 rpm, and the stirring time is 1-5 min; the stirring speed during mixing and cross-linking in step (3) is 100-500 rpm, and the stirring time is 1-5 min.
8. The preparation method according to claim 6 or 7, characterized in that: The filtration is normal pressure filtration for 1-3 hours or vacuum filtration for 5-10 minutes; the drying and molding is hot air drying or vacuum drying, wherein the hot air drying temperature is 25-100°C and the drying time is 5-24 hours; the vacuum drying temperature is 30-60°C and the drying time is 1-8 hours.
9. Use of the bio-based foam material according to any one of claims 1 to 5 as a dielectric layer of a capacitive pressure sensor.
10. A green and environmentally friendly capacitive pressure sensor, characterized in that: The sensor is composed of an upper conductive layer, a lower conductive layer and an intermediate dielectric layer sandwiched therebetween; the intermediate dielectric layer is the bio-based foam material according to any one of claims 1-5.
Citation Information
Patent Citations
Method for preparing foaming buffer packing material
CN106584742A
Method of manufacturing of a foam-formed cellulosic fibre material, sheet and laminated packaging material
CN109803827A
Non-toxic harmless high-mechanical-strength high-elasticity hemicellulose foam composite material and preparation method thereof
CN110903579A
Biodegradable plant fiber-based lightweight high-toughness material and processing technology thereof
CN117946532A
Cellulose foams for high performance insulations
US20200392301A1